Power distribution strategy for a hybrid energy storage system suitable for wind-storage microgrid - LI Yanbo; YANG Kai; CHEN Junshuo; YAO Bobin; LIU Weiyu; WU Qisheng (Diance yu yibiao)
In order to realize the low-carbon development under the double carbon background, solve the problems of multi-energy supply, energy saving and emission reduction of integrated energy system, a low-carbon optimized operation strategy of the integrated energy system including solar thermal power plant and hydrogen energy storage is proposed. By analyzing the combined operation of TES system and hydrogen energy storage system, the multi-energy storage joint supply model is established to effectively realize the mutual transfer of electric-thermal energy, improve energy utilization rate and optimize the operation flexibility of the system. Carbon trading and carbon tax are introduced into system decision-making, and a low-carbon scheduling optimized model of integrated energy system is constructed with the goal of minimizing comprehensive costs such as energy purchase cost, operation and maintenance cost and carbon trading cost. The results show that the coordinated scheduling of TES and hydrogen energy storage can effectively reduce operating costs and carbon emissions. Hybrid energy storage system is one of the important components of microgrid, and studying its power distribution strategy is of great significance for battery protection. Based on a hybrid energy storage system composed of supercapacitors and batteries, a complementary ensemble empirical mode decomposition method is proposed to smooth the power fluctuations caused by the instability of wind power generation. Aiming at the volatility and uncertainty of wind power generation, the complementary ensemble empirical mode decomposition method can decompose the original energy signals of wind power into inherent modal components and margins, and obtain the demarcation point of primary power distribution through energy entropy theory, that is, the initial power distribution. The fuzzy control is used to optimize the state of charge of the hybrid energy storage system, adaptively adjust and modify the power distribution command of the hybrid energy storage system. Using MATLAB program and simulink simulation model combined with example analysis, the results show that the proposed strategy can make the battery SOC fluctuation not more than 8%, and the supercapacitor SOC fluctuation not more than 10%, which effectively improves the work efficiency and service life of the entire system.